A Study of the Demand for Housing by Low Versus High Income Households - Follain, James R. (Journal of Financial and Quantitative Analysis, 1979)
James R. Follain, Jr., A Study of the Demand for Housing by Low Versus High Income Households, The Journal of Financial and Quantitative Analysis, Vol. 14, No. 4, Proceedings of 14th Annual Conference of the Western Finance Association, June 21-23, 1979 (Nov., 1979), pp. 769-782